Method for synthesizing ammonia through lithium mediation and electrolyte used in method

By using lithium-oxide titanium ore electrolyte with deposited precious metal films in the lithium-mediated ammonia synthesis method, the problems of high energy consumption and high temperature and high pressure of traditional ammonia synthesis methods are solved, and efficient ammonia synthesis is achieved under normal pressure, improving the safety and environmental protection of the system.

CN119615274AActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411840469.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional ammonia synthesis methods such as Haber-Bosch process have high energy consumption and high temperature and high pressure operations, resulting in huge environmental and energy consumption. The lithium-mediated ammonia synthesis method is limited in mass transfer of nitrogen and hydrogen in non-aqueous liquid electrolytes, and raw materials need to be supplied with pressurized pressure.

Method used

The lithium oxide titanium ore electrolyte that deposits precious metal films, enhances nitrogen mass transfer through solid lithium-containing electrolytes, and uses water as a hydrogen source to optimize material composition and structural design to achieve efficient lithium ion conduction and good chemical stability.

Benefits of technology

Continuous ammonia production of ammonia under normal pressure improves the efficiency and stability of ammonia synthesis, reduces energy consumption, and improves the safety and environmental protection of the system by using water as a hydrogen source.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of electrochemical ammonia synthesis, in particular to a lithium-mediated ammonia synthesis method and an electrolyte used in the method. The invention discloses a preparation method of a lithium titanium oxide electrolyte deposited with a noble metal film, which comprises the following steps: mixing lithium carbonate and ammonium titanate for solid-phase reaction, placing the obtained lithium titanium oxide (LiTiO2) as a substrate on a sample table of a vacuum cavity of PVD (Physical Vapor Deposition) equipment, starting a vacuum pump and a sputtering source, and depositing the noble metal film. The invention also discloses a lithium-mediated conductive chemical synthesis method for ammonia, which utilizes the lithium titanium oxide electrolyte deposited with the noble metal film. And water is used as a hydrogen source, so that the safety and the stability of the system are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical ammonia synthesis, and in particular to a lithium-mediated ammonia synthesis method and an electrolyte used therein. Background Art

[0002] Ammonia (NH3), as an important chemical raw material and energy carrier, has a wide range of applications in agriculture, chemical industry, energy and other fields. At present, the ammonia produced annually in the world is mainly used to make fertilizers to increase crop yields. In addition, ammonia is also used to produce a variety of chemicals, clean fuels and as a potential hydrogen carrier because it is easy to liquefy, store and transport, has high energy density and carbon-free emissions. However, the traditional ammonia synthesis method, namely the Haber-Bosch process, poses great challenges to the environment and energy consumption due to its high energy consumption and high temperature and high pressure operating environment. Therefore, the development of a low-energy, environmentally friendly ammonia synthesis method has become a hot topic in current research.

[0003] As an emerging ammonia synthesis technology, the lithium-mediated ammonia synthesis method has the potential to achieve ammonia synthesis at room temperature and pressure. This method mainly relies on the high activity of lithium metal to reduce nitrogen (N2) to ammonia through electrochemical reactions. Jens K. et al. (Energy & Environmental Science, 2017, 10 (7): 1621-1630.) reported a novel ammonia production strategy, taking the electrochemical lithium cycle process as an example, which provides a green ammonia synthesis route by directly coupling with renewable electricity. Compared with the traditional aqueous electrochemical method, this method bypasses the hydrogen evolution reaction by using a step-by-step synthesis method. The ammonia synthesis process of this method is divided into electrolysis of LiOH, direct nitridation of Li, and hydrolysis of Li3N to release ammonia to form LiOH again, realizing cyclic ammonia production. However, in non-aqueous liquid electrolytes, the mass transfer process of nitrogen and hydrogen is limited, and pressurization must be applied to ensure the supply of raw materials. In this regard, Wang et al. from the University of Science and Technology of China (CN202410103839.1) proposed a reasonable design, including a reactor based on an all-solid-state lithium-ion symmetric battery, using solid-state lithium-ion membrane materials, and a gas diffusion electrode synthesized in situ on a solid electrolyte. Sustainable proton replenishment is achieved through hydrogen oxidation reaction, and the N≡N triple bond is broken by LiNR reaction, which can continuously produce ammonia for 100h at normal pressure and at a current density of 1000mA / cm 2 The maximum ammonia production was 101.9±7.9nmol / s / cm 2 However, this method uses hydrogen gas as the hydrogen source, and most hydrogen gas comes from fossil fuels, so it still faces energy and environmental problems. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for synthesizing ammonia mediated by lithium and the electrolyte used therein.

[0005] In order to solve the above technical problems, the present invention provides an electrolyte for lithium-mediated synthesis of ammonia: a lithium oxide titanite electrolyte with a deposited noble metal film.

[0006] The present invention also provides a method for preparing a lithium titanium oxide electrolyte for depositing a noble metal film, comprising the following steps:

[0007] 1) Mix lithium carbonate and ammonium titanate in a molar ratio of 1 to 5:1, heat the resulting mixture to 700 to 1000°C (preferably 800 to 900°C) for solid phase reaction for 4±0.5h, and then cool (naturally cool to room temperature) to obtain lithium titanium oxide ore (LiTiO2);

[0008] 2) Place lithium titanium oxide (LiTiO2) as a substrate on the sample stage of the vacuum chamber of the PVD equipment, start the vacuum pump and sputtering source, and deposit the precious metal film. During the deposition process, the deposition rate is controlled to be (0.1±0.01) nm / s and the time is 1000±50s.

[0009] Improvement of the preparation method of lithium titanium oxide electrolyte for depositing precious metal film of the present invention:

[0010] The noble metal is Pd or Pt (i.e., pure Pd or Pt is selected as the target material);

[0011] The sputtering gas was Ar.

[0012] As a further improvement of the method for preparing a lithium titanium oxide electrolyte for depositing a noble metal film of the present invention, in the step 2):

[0013] The temperature is 200±20℃ and the sputtering power is 200±20W.

[0014] As a further improvement of the method for preparing the lithium titanium oxide electrolyte for depositing a noble metal film of the present invention, in step 2):

[0015] The target-substrate distance was set to 80 mm. The vacuum pump and sputtering source were started, and the initial pressure in the vacuum chamber was 5×10 -4 Pa, during the sputtering process, the working pressure in the vacuum chamber is maintained at 0.5Pa, and the noble metal film is deposited. During the deposition process, the substrate temperature is maintained at 200±20℃, the sputtering power is 200±20W, and the deposition rate is (0.1±0.01)nm / s.

[0016] The present invention also provides a method for lithium-mediated electrochemical synthesis of ammonia, using the lithium-titanium oxide electrolyte deposited with a noble metal film obtained by any of the above methods.

[0017] A lithium titanium oxide electrolyte (precious metal-modified lithium titanium oxide ore as an electrolyte) with a deposited precious metal film is placed in an electrolytic cell (water is flown in the electrolytic cell) and connected to a constant potential instrument; high-purity nitrogen (nitrogen with a purity ≥99.999%) is introduced into the electrolytic cell at a flow rate of 100±10sccm, a voltage is applied to initiate ion transport in the electrolyte, a current-time (It) curve is recorded to monitor the electrolysis process, the separated ammonia is collected, and the ammonia yield is analyzed using ion chromatography.

[0018] As an improvement of the lithium-mediated electrochemical synthesis of ammonia method of the present invention: the applied voltage range is -1.0 to 0V.

[0019] The technical solution of the present invention adopts a solid lithium-containing electrolyte, strengthens nitrogen mass transfer, and uses water as a hydrogen source to improve the safety and stability of the system.

[0020] The present invention provides an electrolyte for lithium-mediated ammonia synthesis, that is, provides a new electrolyte material and a preparation method thereof, which achieves efficient lithium ion conduction and good chemical stability by optimizing material composition and structural design, thereby improving the efficiency and stability of lithium-mediated ammonia synthesis.

[0021] The present invention has the following technical advantages:

[0022] 1) Lithium oxide titanite has excellent ionic conductivity and good chemical stability, and can resist the corrosion of reaction products such as water and nitrogen, thereby maintaining its performance and long-term stability.

[0023] 2) After the electrolyte surface is modified with precious metal catalysts (electrodes) such as platinum or palladium, lithium oxide titanium ore can effectively enhance the electrochemical synthesis reaction rate and selectivity of ammonia, and achieve a more efficient catalytic effect by optimizing the interface between the metal electrode and the electrolyte.

[0024] Note: The metal platinum on the surface of the solid electrolyte is equivalent to a catalyst, so it is believed that the electrolyte also has a catalytic function.

[0025] 3) The solid-phase reaction process for preparing lithium oxide titanium ore is relatively mature, and can efficiently control the crystal structure and micromorphology, improve the density and conductivity of the material, and reduce energy consumption and preparation time.

[0026] In summary, the present invention provides an electrolyte for lithium-mediated synthesis of ammonia; specifically, a lithium oxide titanium ore electrolyte with a deposited precious metal film is provided for lithium-mediated synthesis of ammonia. The lithium oxide titanium ore of the present invention has excellent ionic conductivity and good chemical stability. After the electrode surface is modified with a precious metal catalyst such as platinum or palladium, the electrochemical synthesis reaction rate and selectivity of ammonia can be effectively enhanced. The solid phase reaction process is relatively mature, and the crystal structure and micromorphology can be efficiently controlled, the density and conductivity of the material can be improved, and energy consumption and preparation can be reduced. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0028] Example 1: A method for preparing a lithium titanium oxide electrolyte deposited with a precious metal Pd film:

[0029] 1) Mix appropriate amounts of lithium carbonate and ammonium titanate in a 1:1 molar ratio, transfer 5 g of the mixture into a ceramic crucible, place the crucible in a tube furnace, heat it to 800°C (heating rate of 10°C / min), and keep it for 4 hours for solid phase reaction. After the insulation is completed, the furnace is naturally cooled to room temperature. The obtained product is named lithium titanium oxide (LiTiO2);

[0030] 2) Place the lithium titanium oxide ore (LiTiO2) obtained in step 1) as a substrate on the sample stage of the vacuum chamber of the PVD equipment, select pure Pd as the target material, and select Ar gas as the sputtering gas; set the target-substrate distance to 80 mm; start the vacuum pump and sputtering source, and the initial pressure in the vacuum chamber is about 5×10 -4 Pa, during the sputtering process, the working pressure in the vacuum chamber is maintained at 0.5Pa, and the precious metal Pd film is deposited. During the deposition process, the substrate temperature is maintained at 200°C, the sputtering power is 200W, and the deposition rate is 0.1nm / s, until the target (Pd film) thickness is 100nm, that is, the sputtering time is about 1000s. The result is named precious metal Pd modified lithium oxide titanium ore (Pd / LiTiO2), that is, lithium oxide titanium ore electrolyte for depositing precious metal film.

[0031] The target-substrate distance refers to the distance between the target and the substrate during magnetron sputtering.

[0032] Experiment 1: The precious metal Pd-modified Pd / LiTiO2 obtained in Example 1 was placed in an electrolytic cell (with water flowing in the electrolytic cell) as an electrolyte and connected to a potentiostat. High-purity nitrogen (nitrogen with a purity ≥ 99.999%) was introduced into the electrolytic cell at a flow rate of 100 sccm. A voltage of -0.5 V was applied to start ion transport in the electrolyte, and the current-time (It) curve was recorded to monitor the electrolysis process. The separated ammonia was collected and the ammonia yield was analyzed using ion chromatography, and the ammonia yield was 200.5 nmol / s / cm 2 .

[0033] Ammonia production (nmol s -1 cm -2 )=n NH3 / (t×A).

[0034] In the above formula, n NH3 is the molar number of ammonia generated by the test, t is the electrolysis time (2h), A is the contact area between the electrolyte sample and the electrode (5cm 2 ).

[0035] Experiment 2, conductivity test: The Pd / LiTiO2 obtained in Example 1 was made into a thin sheet, and electrodes were clamped on both sides of the sample. The frequency range was set to 10 Hz to 1 MHz, and the impedance spectrum test was performed to record the impedance values ​​of the sample at different frequencies. The measured conductivity was 1.3×10 -3 S / cm.

[0036] Conductivity:

[0037] In the above formula, L is the sample thickness (1.5 mm), R is the measured resistance value, and A is the contact area between the electrolyte sample and the electrode (5 cm 2 ).

[0038] Experiment 3, stability test: In the electrochemical test, the stability of the electrolyte is evaluated by the degree of current decay over a long period of time.

[0039] The Pd / LiTiO2 modified with the noble metal Pd obtained in Example 1 was placed in an electrolytic cell as an electrolyte and connected to a constant potential instrument. High-purity nitrogen (nitrogen with a purity of ≥99.999%) was introduced into the electrolytic cell at a flow rate of 100 sccm and an applied voltage of -0.5 V. The current-time (It) curve under long-term (200 h) electrolysis conditions was recorded. The resulting current attenuation was 2.5%.

[0040] Current attenuation degree = (I 初始 -I 最终 ) / I 初始 ×100%.

[0041] Example 2-1: Compared with Example 1, the molar ratio of lithium carbonate and ammonium titanate is changed from "1:1" to "2:1", and the total amount remains unchanged, which is still 5g; the rest is the same as Example 1.

[0042] The precious metal Pd-modified lithium oxide titanium ore obtained in Example 2-1 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 180.4 nmol / s / cm 2 .

[0043] The precious metal Pd-modified lithium oxide titanium ore obtained in Example 2-1 was tested according to the method described in Experiment 2, and the conductivity obtained was 1.6×10 -3 S / cm.

[0044] The precious metal Pd-modified lithium titanium oxide ore obtained in Example 2-1 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 3.6%.

[0045] Example 2-2: Compared with Example 1, the molar ratio of lithium carbonate and ammonium titanate is changed from "1:1" to "5:1", and the total amount remains unchanged, which is still 5g; the rest is the same as Example 1.

[0046] The precious metal Pd-modified lithium titanium oxide obtained in Example 2-2 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 176.2 nmol / s / cm 2 .

[0047] The precious metal Pd-modified lithium oxide titanium ore obtained in Example 2-2 was tested according to the method described in Experiment 2, and the conductivity obtained was 1.7×10 -3 S / cm.

[0048] The precious metal Pd-modified lithium titanium oxide ore obtained in Example 2-2 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 3.8%.

[0049] Embodiment 3: Compared with Embodiment 1, the temperature in step 1) is changed from "800° C." to "900° C."; the rest is the same as Embodiment 1.

[0050] The precious metal Pd-modified lithium titanium oxide obtained in Example 3 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 194.1 nmol / s / cm 2 .

[0051] The precious metal Pd-modified lithium titanium oxide obtained in Example 3 was tested according to the method described in Experiment 2, and the conductivity obtained was 2.1×10 -3 S / cm.

[0052] The precious metal Pd-modified lithium titanium oxide ore obtained in Example 3 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 4.1%.

[0053] Example 4. Compared with Example 1, the "deposition of precious metal Pd film" in step 2) is changed to "deposition of precious metal Pt film", that is, step 2) is specifically changed as follows: "selecting pure Pd as the target material" is changed to "selecting pure Pt as the target material", and the rest is the same as Example 1.

[0054] The precious metal Pt-modified lithium titanium oxide obtained in Example 4 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 169.8 nmol / s / cm 2 .

[0055] The precious metal Pt-modified lithium titanium oxide obtained in Example 4 was tested according to the method described in Experiment 2, and the conductivity obtained was 1.7×10 -3 S / cm.

[0056] The precious metal Pt-modified lithium titanium oxide ore obtained in Example 4 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 3.2%.

[0057] Comparative Example 1: relative to Example 1, relative to Example 1, the temperature in step 1) is changed from "800° C." to "500° C."; the rest is the same as Example 1.

[0058] The lithium titanium oxide ore modified with precious metal Pd obtained in Comparative Example 1 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 69.2 nmol / s / cm 2 .

[0059] The precious metal Pd-modified lithium titanium oxide obtained in Comparative Example 1 was tested according to the method described in Experiment 2, and the conductivity was 9.6×10 -3 S / cm.

[0060] The lithium titanium oxide ore modified with precious metal Pd obtained in Comparative Example 1 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 18.2%.

[0061] Comparative Example 2: Compared with Example 1, the molar ratio of lithium carbonate and ammonium titanate was changed from "1:1" to "20:1", and the total amount remained unchanged, still 5 g; the rest was the same as Example 1.

[0062] The lithium titanium oxide modified with precious metal Pd obtained in Comparative Example 2 was tested according to the method described in Experiment 1, and the ammonia yield obtained was 90.4 nmol / s / cm 2 .

[0063] The precious metal Pd-modified lithium titanium oxide obtained in Comparative Example 2 was tested according to the method described in Experiment 2, and the conductivity was 5.6×10 -4 S / cm.

[0064] The lithium titanium oxide ore modified with precious metal Pd obtained in Comparative Example 2 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 21.3%.

[0065] Comparative Example 3, relative to Example 1, "depositing precious metal Pd film" is changed to "depositing metal Cu film", that is, step 2) is specifically changed as follows: "selecting pure Pd as the target material" is changed to "selecting pure Cu as the target material", and the rest is the same as Example 1.

[0066] The Cu-modified lithium titanium oxide obtained in Comparative Example 3 was tested according to the method described in Experiment 1, and the ammonia yield was 90.4 nmol / s / cm 2 .

[0067] The Cu-modified lithium titanium oxide ore obtained in Comparative Example 3 was tested according to the method described in Experiment 2, and the conductivity was 9.5×10 -4 S / cm.

[0068] The metal Cu-modified lithium titanium oxide ore obtained in Comparative Example 3 was tested according to the method described in Experiment 3, and the current attenuation degree obtained was 26.4%.

[0069] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. An electrolyte for lithium-mediated ammonia synthesis, characterized in that: It is a lithium oxide titanium ore electrolyte with a deposited precious metal film.

2. A method for preparing a lithium titanium oxide electrolyte deposited with a noble metal film, characterized in that The steps include: 1) Mix lithium carbonate and ammonium titanate in a molar ratio of 1 to 5:1, heat the resulting mixture to 700 to 1000°C for solid phase reaction for 4±0.5h, and then cool to obtain lithium oxide titanate; 2) Place lithium oxide titanium ore as a substrate on the sample stage of the vacuum chamber of the PVD equipment, start the vacuum pump and sputtering source, and deposit the precious metal film. During the deposition process, the deposition rate is controlled to be (0.1±0.01) nm / s and the time is 1000±50s.

3. The method for preparing a lithium titanium oxide electrolyte for depositing a noble metal film according to claim 2, characterized in that: The noble metal is Pd or Pt; The sputtering gas was Ar.

4. The method for preparing a lithium titanium oxide electrolyte for depositing a noble metal film according to claim 3, characterized in that In the step 2): The temperature is 200±20℃ and the sputtering power is 200±20W.

5. The method for preparing a lithium titanium oxide electrolyte for depositing a noble metal film according to claim 4, characterized in that In the step 2): The target-substrate distance was set to 80 mm. The vacuum pump and sputtering source were started, and the initial pressure in the vacuum chamber was 5×10 -4 Pa, during the sputtering process, the working pressure in the vacuum chamber is maintained at 0.5Pa, and the noble metal film is deposited. During the deposition process, the substrate temperature is maintained at 200±20℃, the sputtering power is 200±20W, and the deposition rate is (0.1±0.01)nm / s.

6. A method for lithium-mediated electrochemical synthesis of ammonia, characterized in that: A lithium titanium oxide electrolyte deposited with a noble metal film obtained by any one of claims 2 to 5, The lithium titanium oxide electrolyte with a deposited precious metal film is placed in an electrolytic cell and connected to a constant potential instrument; high-purity nitrogen is introduced into the electrolytic cell at a flow rate of 100±10sccm, a voltage is applied to start ion transport in the electrolyte, and the separated ammonia is collected.

7. The method for lithium-mediated electrochemical synthesis of ammonia according to claim 6, characterized in that: The applied voltage range is -1.0 to 0V.

Citation Information

Patent Citations

  • A full solid-state lithium ion membrane reactor with symmetrical structure and application thereof

    CN117867536B

  • Method for preparing anode composite material of palladium (Pd)-containing lithium ion secondary battery

    CN102931387A

  • Hollow spherical LiTiO2 material and preparation method thereof

    CN104393274A

  • Graphene-lithium titanate composite material and preparation method thereof, lithium-supplementing graphene-lithium titanate film and lithium battery

    CN107785559A

  • Composite ionic conducting electrolytes

    TW201304240A